Electron beam-induced writing of nanoscale iron wires on a functional metal oxide - Vollnhals, Florian; Woolcot, Tom; Walz, Marie-Madeleine; Seiler, Steffen; Steinrück, Hans-Peter; Thornton, Geoff; Marbach, Hubertus (Journal of Physical Chemistry C, 2013)
Electron beam-induced surface activation (EBISA) has been used to grow wires of iron on rutile TiO(110)-(1 × 1) in ultrahigh vacuum. The wires have a width down to ∼20 nm and hence have potential utility as interconnects on this dielectric substrate. Wire formation was achieved using an electron beam from a scanning electron microscope to activate the surface, which was subsequently exposed to Fe(CO). On the basis of scanning tunneling microscopy and Auger electron spectroscopy measurements, the activation mechanism involves electron beam-induced surface reduction and restructuring. © 2013 American Chemical Society.